Penyuluhan Manfaat Magnesium terhadap Kesehatan Jiwa - Juni Chudri; Lily Marliany Surjadi; Revalita Wahab; Astri Handayani; Fransisca Chondro (CV. Multi Kreasi Media, 2022)
On March 2019, WHO declared COVID-19 as a pandemic. In order to control the transmission of this disease, governments made some policies to restrict the activities of their citizens. These restrictions had impact not only in economics but also in health sector since the restriction produce a psychological burden for the people. Study by Lai et al in Wuhan, China showed that there was an increase in the prevalence of depression (50.4%), anxiety (44.6%), insomnia (34%), and also pessimism (71.5%). One of the factors that influenced the mental health is nutritional intake. An adequate intake of nutrients in our daily life can help maintaining the hormonal balance. Magnesium is one of the important nutrients that help maintaining the mental health. Food containing magnesium can be easily found, but the lack of knowledge regarding the importance of Magnesium causing the low daily intake of Magnesium in Indonesian population. Since, Magnesium is important for our mental health, so it is very important to do the counseling about Magnesium to increase the knowledge of people. Hopefully, by the increase of the knowledge, the daily intake of Magnesium will increase and these will lead to the better mental-health quality of the population of Indonesia.